Comparative study of the cytolytic activity of snake venoms from African spitting cobras (Naja spp., Elapidae) and its neutralization by a polyspecific antivenom - Méndez Madriz, Ileana Sofía (2011)
Versión final embargada hasta 2081-11 por política editorial